Alterações fitotécnicas em genótipos de cafeeiro Conilon em resposta ao sombreamento - Torres, Cassio Fernandes (2020)
The coffee tree can be grown in different environments due to its phenotypic plasticity, as well as the existence of pre-selected genotypes. The benefits provided by shading, associated with morphological, physiological and nutritional modulations can be